(untitled) (International Journal of Engineering and Computer Science, 2017)
Mobile phone cloning is a technique wherein security data from one mobile phone is transferred into another phone. The other mobile phone becomes the exact replica of the original cell phone like a clone. As a result, while calls can be made from both phones, only the original is billed. Though communication channels are equipped with security algorithms, yet cloners get away with the help of loop holes in systems. So when one gets huge bills, the chances are that the phone is being cloned.(1) Cloning CDMA cell phones(2)A Pattern Recognition Technique is used to classify the telephone users into classes in order to identify if a call does not correspond to the patterns of a specific user; and (3) Distributed Object Technique is used for the implementation of this distributed system (i.e., manager and agents).